Insect-Induced Conifer Defense. White Pine Weevil and Methyl Jasmonate Induce Traumatic Resinosis, de Novo Formed Volatile Emissions, and Accumulation of Terpenoid Synthase and Putative Octadecanoid Pathway Transcripts in Sitka Spruce - Miller, Barbara (American Society of Plant Biologists, 2005)
Stem-boring insects and methyl jasmonate (MeJA) are thought to induce similar complex chemical and anatomical defenses in conifers. To compare insect- and MeJA-induced terpenoid responses, we analyzed traumatic oleoresin mixtures, emissions of terpenoid volatiles, and expression of terpenoid synthase (TPS) genes in Sitka spruce (Picea sitchensis) following attack by white pine weevils (Pissodes strobi) or application of MeJA. Both insects and MeJA caused traumatic resin accumulation in stems, with more accumulation induced by the weevils. Weevil-induced terpenoid emission profiles were also more complex than emissions induced by MeJA. Weevil feeding caused a rapid release of a blend of monoterpene olefins, presumably by passive evaporation of resin compounds from stem feeding sites. These compounds were not found in MeJA-induced emissions. Both weevils and MeJA caused delayed, diurnal emissions of (−)-linalool, indicating induced de novo biosynthesis of this compound. TPS transcripts strongly increased in stems upon insect attack or MeJA treatment. Time courses and intensity of induced TPS transcripts were different for monoterpene synthases, sesquiterpene synthases, and diterpene synthases. Increased levels of weevil- and MeJA-induced TPS transcripts accompanied major changes in terpenoid accumulation in stems. Induced TPS expression profiles in needles were less complex than those in stems and matched induced de novo emissions of (−)-linalool. Overall, weevils and MeJA induced similar, but not identical, terpenoid defense responses in Sitka spruce. Findings of insect- and MeJA-induced accumulation of allene oxide synthase-like and allene oxide cyclase-like transcripts are discussed in the context of traumatic resinosis and induced volatile emissions in this gymnosperm system.